Frequency of Thalassemia Minor and Iron Deficiency Anemia in Pregnant Women Presenting with Anemia - Nawaz, Maria; Naveed, Parveen; Nawaz, Hassan (Indus Journal of Bioscience Research, 2025)
Background: Anemia in pregnancy is a significant public health concern, affecting maternal and fetal health outcomes. Among its causes, iron deficiency anemia and thalassemia minor are critical conditions requiring early diagnosis and management. Identifying the prevalence and associated factors of these anemia types is essential for improving antenatal care and preventing complications. Objective: To determine the prevalence of thalassemia minor and iron deficiency anemia in pregnant women with anemia. Study Design: Cross-sectional study. Duration and Place of Study: This study was conducted from September 2024 to December 2024 in the Obstetrics and Gynaecology Department of Saidu Group of Teaching Hospitals, Swat. Methodology: A total of 130 pregnant women aged 18–40 years with a confirmed singleton pregnancy beyond 12 weeks of gestation and diagnosed with anemia were enrolled using a non-probability consecutive sampling method. Patients with hypertensive disorders, gestational diabetes, autoimmune diseases, or hematological disorders other than anemia were excluded. Demographic and clinical data, including hemoglobin (Hb) concentration, serum ferritin, and mean corpuscular volume (MCV), were recorded. Results: The mean age of participants was 30.21 ± 3.25 years, with a gestational age of 17.15 ± 3.07 weeks. The prevalence of iron deficiency anemia was 27.7%, while 6.2% of participants were diagnosed with thalassemia minor. Conclusion: Thalassemia minor and iron deficiency anemia are prevalent among anemic pregnant women, with distinct demographic and clinical associations.